FACTORS ANALYSIS OF AFFECTING THE QUALITY OF GOVERNMENT FINANCE SUBSIDIARIES (Empirical Study Payakumbuh Government) - Lisa Amelia Herman; Daswirman Daswir (JURNAL PUNDI, 2017)
This study aimed to test: 1) Effect of implementation of financial management information system to quality LKPD, 2) Effect of human resource competencies to quality LKPD, and 3) Influence of Role SPIP to quality LKPD. This type of research is classified at the research be cuantitatife. The population in this study are 10 work units (SKPD) in Payakumbuh. Selection of the sample with purposive sampling method, the number of respondents 100. The data used in this study of primary data. Data collection techniques with engineering survey by distributing questionnaires to Employees Finance, General and Human Resources, Division of Program and Admin SIPKD. The analytical method used is path analysis with SPSS. The research proves that 1) Implementation of Financial Management Information System positive significant effect on the quality of LKPD where significant value of 0.007> 0.05. β coefficient value in the variable X1 is positive which means that (H1 accepted). 2) HR Competency positive significant effect on the quality of LKPD where significant value of 0.002> 0.05. β coefficient value in the variable X2 is positive which means that (H2 accepted). 3) SPIP positive significant effect on the quality of LKPD where significant value of 0.000> 0.05. β coefficient value in the variable X3 is positive which means that (H3 accepted).